Development of Efficient Micropropagation Protocols of Elite Accessions of Jatropha curcas L. - Naresh, B.; Dhanasri, G.; Reddy, M Srikanth; Cherku, Prathibha Devi (Plant Tissue Culture and Biotechnology, 2014)
Efficient micropropagation protocols were developed from explants of two accessions of Jatropha curcas L. viz. Rain Shadow Area Development (RSAD) department and Karimnagar (KM). Adventitious shoots were regenerated with higher frequency on medium-A from cotyledonary node explants, than those from axillary node and shoot-tip explants. Shoots were also regenerated from calluses developed from cotyledonary node and shoot-tip explants on medium-B. Regenerated shoots were rooted on medium-G, transplanted to pots and later transferred to field. Somatic embryos developed on embryogenic calluses produced from cotyledonary node explants on medium-C were converted to plantlets on medium-F and transferred to pots. Out of the 199 plants established in the Botanical Garden, 118 plants were developed from cotyledonary node explants, which indicates that they are the most suitable explants for micropropagation of Jatropha. D. O. I. http://dx.doi.org/10.3329/ptcb.v23i2.17524 Plant Tissue Cult. & Biotech. 23(2): 231-239, 2013 (December)